Effect of harmane, an endogenous beta-carboline, on learning and memory in rats - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Our aim was to investigate the effects of acute harmane administration upon learning and memory performance of rats using the three-panel runway paradigm and passive avoidance test. Male rats received harmane (2.5, 5, and 7.5 mg/kg, i.p.) or saline 30 min. before each session of experiments. In the three panel runway paradigm, harmane did not affect the number of errors and latency in reference memory. The effect of harmane on the errors of working memory was significantly higher following the doses of 5 mg/kg and 7.5 mg/kg. The latency was changed significantly at only 7.5 mg/kg in comparison to control group. Animals were given pre-training injection of harmane in the passive avoidance test in order to determine the learning function. Harmane treatment decreased the retention latency significantly and dose dependently, which indicates an impairment in learning. In this study, harmane impaired working memory in three panel runway test and learning in passive avoidance test. As an endogenous bioactive molecule, harmane might have a critical role in the modulation of learning and memory functions. (c) 2012 Elsevier Inc. All rights reserved.
Keywords: Harmane; Learning; Memory; Three panel runway; Passive avoidance; Rats; PASSIVE-AVOIDANCE TEST; WORKING-MEMORY; BENZODIAZEPINE RECEPTORS; INHIBITORY AVOIDANCE; CHOLINERGIC SYSTEM; INDUCED AMNESIA; BRAIN; MICE; ACQUISITION; INVOLVEMENT